Qualitative Study of the Cross-Cultural Adaptation of Macao Students in Mainland China - Chia-Wen Lee; Weidong Wu; Zhi-Yu Tan; Cheng-Fu Yang (MDPI AG, 2020)
Education research is increasingly paying attention to students' cross-cultural adaption in Mainland China. As a special administrative region of China, educational systems and language of instruction of Macao are different from those of Mainland China. This study analyzes the cross-cultural adaptation of Macao students in Mainland China by using qualitative semi-structured interviews. The results show that study motivation, medium of instruction, and social integration are important factors determining how Macao students adapt to university programs. Failure to adapt to the language of instruction is the most direct, prominent, and enduring problem that Macao students encounter when studying in the Mainland. The current study's findings have practical implications for faculties who provide support and training to Macao students in Mainland China. The study discovers that strengthening the Mandarin language skills of Macao students is currently a priority.